Apollo 13 - Herman, Gail; Nang Chan Yeema (New York, USA Grosset & Dunlap Publisher, 1995)
Apollo 13 is an exciting movie but it was also a true story. Now you can learn the story behind the movie. The story of the race to space. The race to the moon, the space race.
Keywords: Level Books